Legalization of Same-Sex Marriage in terms of Islamic Law: a Comparative Study of Indonesia and Germany - Nazar, Muhamad; Sjaiful, Muhammad; Zahrowati, Zahrowati (Universitas Negeri Gorontalo, 2024)
Marriage is the behavior of creatures created by God Almighty so that life in the natural world develops well. Marriage is recommended and regulated in Islam because it has a noble purpose. As time progresses, marriages which were initially only carried out by heterosexual couples are now seeing the emergence of the phenomenon of same-sex marriages or marriages by LGBT people. What is worrying is that the LGBT phenomenon is growing rapidly in Indonesia due to increasingly open freedoms. This raises pros and cons. Same-sex marriage in Indonesia, a Muslim-majority country, has caused controversy and is considered illegal deviant behavior. However, there are also several countries in the world that have legalized same-sex marriage, including Germany, where Muslims are a minority. In 2017, Germany officially passed regulations regarding same-sex marriage including the right to adopt children. This research aims to conduct a comparative analysis of the topic of same-sex marriage among LGBT actors in Germany and Indonesia using a socio-legal approach. This research has the results of a study that the phenomenon of same-sex marriage by LGBT people that occurs in Germany and Indonesia are two different things and cannot be equated. Several factors behind this are the socio-cultural context which causes society's reactions and the implementation of government regulations regarding same-sex marriage to be different.